Pengaruh Social Media Marketing Activities terhadap Consumer Brand Engagement : (Studi pada Akun TikTok @alfamartku) - Nina Nuraeni; Adam Hermawan; Btari Mariska Purwaamijaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the influence of social media marketing activities on Consumer Brand Engagement on TikTok @alfamartku. The data of this study was obtained from the results of the distribution of a questionnaire with a population sample of 100 respondents processed using SPSS 29. The findings of this study show that there is a positive influence of the variable of social media marketing activities on Consumer Brand Engagement partially, with an R-Square value of 58.9% indicating that most of the variation in Consumer Brand Engagement can be explained by marketing activities on TikTok social media. Trendiness has a strong influence on social media marketing activities, while the Electronic Word of Mouth (EWOM) indicator has a lower influence. Furthermore, the indicator that has the strongest influence on the Consumer Brand Engagement variable is Cognitive Processing, while the indicator that has the lowest influence is Affection. These findings underscore the importance of effective marketing strategies on social media in building strong engagement between brands and consumers.